Approaches in Forming Informational Competence of Secondary School Teachers. - I.G. Kislaya (Ìнформаційні технології в освіті)
One of the main problems of realization of competence approach in the system of secondary education is the creation of generally accepted methods of forming key competences of teachers. In the article main points and structure of the concept of informational competence of a high school teacher and means of school informational analytical system that will provide necessary conditions for extension of informational competence of teachers of different subjects of a school cycle creation are exposed.